Formulation and Evaluation of instant granules from Ketapang Badak fruit (Ficus lyrata Warb) using wet granulation method as an antioxidant supplement - Norisca Aliza Putriana; Efri Mardawati; Yoga Windu Wardhana; Nurul Afifah; Anting Wulandari; Dwi Wahyudha Wira; Nanang Masruchin (Indonesian Journal of Pharmaceutics, 2021)
Free radicals are naturally produced from the body's metabolic processes, but the excessive amount of free radicals can interfere with human health because they cause oxidative stress. Therefore we need antioxidants that can protect against free radicals. Ficus lyrata W. is one of the antioxidant sources. This study aims to formulate instant granules from the Ethanol extract of Ficus lyrata W. using the wet granulation method. The formula is optimized using the Design Expert with the two-level factorial method. The optimized factors are xanthan gum 0,8-1,5% and PVP 0,5-5%. Granules are evaluated and analyzed using a Design Expert. The results obtained showed that Formula 4 with a combination of xanthan gum 0,8% and PVP 5% is the best formula, which the evaluation result is Loss On Drying (LOD) 3,28%, Flowability 16.043 ± 0.221 (g/s), Angle of Rest 21.77 ± 0.862, no precipitate for15 minutes, pH = 4.7, dispersed in 31 seconds and sedimentation time is 52.213 ± 1.7878 (minutes), the results of the antioxidant activity test of the ethanol extract of Ficus lyrata is 38,27 µg/ml, and instant granules is 145,02 µg/ml.Keywords: Antioxidant, Ficus lyrata W., Instant granules, Design expert